SEJARAH KENABIAN DALAM BIBEL DAN AL-QURAN - Eko Nopriyansa (UIN Sunan Kalijaga Yogyakarta, 2019)
ABSTRACT The development of science and science in this era facilitated and assisted researchers and interested in religious studies in carrying out the needs of religious research, but Pro-Counter in religious studies became an interesting spotlight throughout history ranging from intellectuals who tried to present a more compromise approach to scientists who used an approach contradictory, disagreement in explaining various problems in Theology, social fields, religious fields, political fields, historical fields and other fields as vital objects in religious concepts is a big problem when researchers show a very subjective character. This paper attempts an in-depth study in answering various issues and misunderstanding in understanding the values of equality contained in the Biblical and Al-Qur'an texts, especially in discussing the historical perspective which is discussed by the two holy books of Muslims and Christians as the two largest religions in the world. Keywords : Prophetic History, The Bible and the Qur'an,